2019
DOI: 10.1016/j.isci.2019.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Development and Genome Sequencing of a Laboratory-Inbred Miniature Pig Facilitates Study of Human Diabetic Disease

Abstract: Pig has been proved to be a valuable large animal model used for research on diabetic disease. However, their translational value is limited given their distinct anatomy and physiology. For the last 30 years, we have been developing a laboratory Asian miniature pig inbred line (Bama miniature pig [BM]) from the primitive Bama xiang pig via long-term selective inbreeding. Here, we assembled a BM reference genome at full chromosome-scale resolution with a total length of 2.49 Gb. Comparative and evolutionary gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 136 publications
1
39
0
Order By: Relevance
“…Finally, we generated a high-contiguous, chromosome-scale and phased assembly of the Luchuan genome, yielding a 2.58 Gb primary assembly with a contig N50 of 18.03 Mb and a scaffold N50 of 140.09 Mb. This assembly is comparable in quality to the Duroc genome [7] and much better than other published pig genomes [4, 810] (Table 1). Remarkably, the alternative haplotig assembly size is very close to the primary assembly with a contig N50 of 17.77 Mb and a scaffold N50 of 140.08 Mb.…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…Finally, we generated a high-contiguous, chromosome-scale and phased assembly of the Luchuan genome, yielding a 2.58 Gb primary assembly with a contig N50 of 18.03 Mb and a scaffold N50 of 140.09 Mb. This assembly is comparable in quality to the Duroc genome [7] and much better than other published pig genomes [4, 810] (Table 1). Remarkably, the alternative haplotig assembly size is very close to the primary assembly with a contig N50 of 17.77 Mb and a scaffold N50 of 140.08 Mb.…”
Section: Resultsmentioning
confidence: 66%
“…The present pig reference genome (Sscrofa11.1) was derived from a Western breed (Duroc pig) [7] with high continuity and quality. Increased accessibility to short-read sequencing has resulted in a deluge of genome assemblies for Chinese indigenous pigs, although incomplete and fragmented compared with Duroc [4, 810]. Until now, no chromosome-level phased assemblies of Chinese indigenous pigs have been built, so accurately investigating the full range of genetic variations and phased diploid architecture is extremely difficult.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of SMRT sequencing offers access to more complete full-length transcriptome data, as has been recently reported (Sharon et al, 2013;Dotterweich et al, 2016). For instance, a study about the full-length transcriptome of diabetic pig models showed multiple genetic alterations that could contribute to diabetic diseases (Zhang et al, 2019). However, the method of PacBio long-read sequencing could not be directly used to quantify gene expression, which still need RNA-seq for quantitative analysis of transcripts (Chen et al, 2017;Jia et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The miniature pig shares many anatomical and physiological features with humans and has been used as an animal model in biomedical research, resulting in great contributions to the medical advances of human beings [ 21 ]. Recently, studies on chronic renal failure [ 22 ], progressive hearing loss [ 23 ], and diabetes [ 24 ] were conducted on Bama pigs. Of the Chinese indigenous miniature pig breeds, the genome of the Wuzhishan pig was the first to be assembled at the scaffold level [ 19 ].…”
Section: Introductionmentioning
confidence: 99%